Effect of Thrombolysis on Circulating Microparticles in Patients with ST-Segment Elevation Myocardial Infarction - Zhe Li; Wei Zhang; Qun-Rang Wang; Yu-juan Yang; Xin-Hong Liu; Gong Cheng; Feng-Jun Chang (Cardiovascular Therapeutics)
Objective. We demonstrated that circulating microparticles (MPs) are increased in patients with coronary heart disease (both chronic coronary syndrome (CCS) and acute coronary syndrome). Whether thrombolysis affects MPs in patients with ST-segment elevation myocardial infarction (STEMI) with or without percutaneous coronary intervention (PCI) is unknown. Methods. This study was divided into three groups: STEMI patients with thrombolysis (n=18) were group T, patients with chronic coronary syndrome (n=20) were group CCS, and healthy volunteers (n=20) were the control group. Fasting venous blood was extracted from patients in the CCS and control groups, and venous blood was extracted from patients in the T group before (pre-T) and 2 hours after (post-T) thrombolysis. MPs from each group were obtained by centrifugation. After determining the concentration, the effects of MPs on endothelial nitric oxide synthase (eNOS) and inducible nitric oxide synthase (iNOS) in rat myocardial tissue in vitro were detected by immunohistochemistry and western blotting. Changes in nitric oxide (NO) and oxygen free radicals (O2•–) were also detected. The effect of MPs on vasodilation in isolated rat thoracic aortae was detected. Results. Compared with that in the control group (2.60±0.38 mg/ml), the concentration of MPs was increased in patients with CCS (3.49±0.72 mg/ml) and in STEMI patients before thrombolysis (4.17±0.58 mg/ml). However, thrombolysis did not further increase MP levels (post-T, 4.23±1.01 mg/ml) compared with those in STEMI patients before thrombolysis. Compared with those in the control group, MPs in both CCS and STEMI patients before thrombolysis inhibited the expression of eNOS (both immunohistochemistry and western blot analysis of phosphorylation at Ser1177), NO production in the isolated myocardium and vasodilation in vitro and stimulated the expression of iNOS (immunohistochemistry and western blot analysis of phosphorylation at Thr495), and the generation of O2•– in the isolated myocardium. The effects of MPs were further enhanced by MPs from STEMI patients 2 hours after thrombolysis. Conclusion. Changes in MP function after thrombolysis may be one of the mechanisms leading to ischemia–reperfusion after thrombolysis.